Trypanocidal drug resistance in four regions of Cote d'Ivoire: Importance and possible impact on sustainability of integrated strategies for trypanosomiasis control - D'Ieteren, G.D.M.; Coulibaly, L.; Atse, P.A.; Hecker, P.A.; Krebs, H.A.; Rowlands, G.J.; Leak, S.G.A.; Nagda, S.M. (OAU/STRC, 1995)
The efficacies of three trypanocidal drugs, diminazene aceturate, isometamidium chloride and homidium bromide, were evaluated in four representative areas of Cote d'Ivoire with different production systems, degree of integration of different trypanosomosis control approaches and delivery of veterinary inputs. Herds were selected as follows: (i) twelve traditional, sedentary herds around Boundiali with a mixture of cattle genotypes, dominantly crosses between trypanotolerant and trypanosusceptible cattle: (ii) eleven groups of Zebu cattle at the Ferkessedougou feedlot, originating dominantly from Mali at the time of the experiments; (iii) fifteen private N'Dama cattle herds in the Bouake area: (iv) sixteen herds of N'Dama cattle at the Marahouse State Ranch. Groups of animals or herds in the four locations were systematically treated with one of the three drugs at given doses (3.5 mg/kg or 7 mg/kg for diminazene aceturate, 0.5 or 1 mg/kg for isometamidium chloride and 1 mg/kg for homidium bromide. Screening for relapse of infection post treatment was done either at 3 week intervals in three sites, or at monthly intervals in the Boundiali area by the buffy coat parasite detection technique. Failures of at least one of the three drugs to control trypanosome infection were observed to a vary ing degree in all but one location. Table 1 indicates the frequency of recurrent infections in the four regions. There was evidence of drug resistance for all three drugs in Boundiali (Coulibaly et al., this volume), for diminazene aceturate and isometamidium chloride, the two drugs tested in Ferkessedougou (Atse et al., this volume), and for homidium bromide in Bouake. Most parasitaemias detected in cattle in Boundiali were associated with T. vivax (86 percent). The prevalence of T. congolense had previously been reduced through the introduction of tsetse control in the location. Trypanosoma vivax was also more prevalent than T. congolense in cattle sampled at Ferkessedougou. Further south T. congolense was the dominant species and in one herd in Bouake with a high prevalence of trypanosomes a large number of relapses occurred to homidium bromide. At Marahoue Ranch the prevalence of recurrent infection was less than 5 percent. In conclusion: there was evidence for resistance to all three trypanocidal drugs at Boundiali and to isometamidium at Ferkessedougou in cattle imported from southern Mali; at Ferkessedougou, a dose of 7 mg/kg body weight seemed necessary for successful application of diminazene; both T. congolense and T. vivax species appeared to express resistance to the three trypanocidal drugs in the tsetse controlled area of Boundiali, it might be difficult to control the residual T. vivax population; further south, there was less evidence of resistance to the three trypanocidal drugs, except possible for homidium at Bouake. The self-cure ability of the N'Dama may have helped to prevent evidence for drug resistance being revealed in this area.